Graphene oxide / lithium iron phosphate composite material and preparation method thereof
By using the composite of graphene oxide and lithium iron phosphate, M-ZIF/S co-doping and thiol-modified graphene oxide in LiFePO4 positive electrode material, the problems of low conductivity and poor lithium ion diffusion rate of LiFePO4 positive electrode material are solved, and the electrochemical performance and cyclic stability of the battery are significantly improved.
Patent Information
- Application Number
- CN202510406750.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-02
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-04-02
AI Technical Summary
LiFePO4 positive electrode material has problems such as low electronic conductivity, poor lithium ion diffusion rate, low tap density and poor cycling performance under high current, which affects its electrochemical performance.
Graphene oxide is used to recombinate with lithium iron phosphate material, and the conductivity and lithium ion diffusion rate of the material are improved by M-ZIF/S co-doping and thiol-modified graphene oxide.
The overall conductivity and electrochemical performance of graphene oxide/lithium iron phosphate composite materials are significantly improved, and the capacity and cycle life of the battery are enhanced.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium iron phosphate materials, and in particular relates to a graphene oxide / lithium iron phosphate composite material and a preparation method thereof. Background Art
[0002] As a form of energy storage, batteries have been widely used in fields such as electric vehicles and hybrid vehicles. However, traditional lead-acid batteries and nickel metal batteries cannot meet market demand due to their low energy density and environmental pollution issues. Lithium batteries are ahead of most other energy storage technologies due to their environmentally friendly characteristics. Among them, lithium iron phosphate batteries have become one of the most widely used secondary batteries for electric vehicles and energy storage due to their high theoretical capacity (170 mAh / g), long life, high operating voltage (3.5 V), high safety, environmental protection and high thermal stability.
[0003] However, LiFePO4 cathode materials also have the following problems: low electronic conductivity (about 10-11S / cm), poor lithium ion diffusion rate, low tap density (3.6g / cm 3 ), poor rate cycling performance at high current. These are the main reasons for the poor electrochemical performance of LiFePO4. In order to overcome these obvious shortcomings, many studies have been conducted in the doping and preparation process, such as heterogeneous doping of LiFePO4, transition metal doping, conductive polymer coating of LiFePO4, and high electronic conductive material coating (mainly carbon). Among them, carbon coating is a simple and effective method to improve the performance of LiFePO4.
[0004] A patent application with publication number CN 115924899 A discloses a method for preparing a lithium iron phosphate / graphene oxide composite material. The application improves the comprehensive performance of the lithium iron phosphate material in lithium battery applications by mixing an iron source with polyamino cellulose oxide; limiting the ratio of lithium and iron elements and the particle size of the lithium source, thereby solving the problem of poor comprehensive performance of lithium iron phosphate materials applied to batteries in the prior art. However, the dispersibility of graphene oxide and lithium iron phosphate needs to be improved, thereby further improving the comprehensive performance of the battery. Summary of the invention
[0005] The object of the present invention is to provide a graphene oxide / lithium iron phosphate composite material and a preparation method thereof, so as to improve the cyclability of the graphene oxide / lithium iron phosphate composite material when applied to batteries.
[0006] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a graphene oxide / lithium iron phosphate composite material comprises the following steps: S1. Add deionized water and hexadecyltrimethylammonium bromide to ethylene glycol and stir evenly to obtain a solution; mix part of the solution with LiOH·H2O and H3PO4, adjust the pH, stir evenly, then add FeSO4·7H2O, Na2S2O3 and ascorbic acid, mix evenly to obtain a mixed solution; mix the remaining solution with a transition metal salt and 2-methylimidazole, heat and stir, centrifuge and wash to obtain M-ZIF; add M-ZIF to the mixed solution, heat and stir, wash and dry to obtain M-ZIF / S-doped LiFePO4 precursor; S2, mixing graphene oxide, N-hydroxysuccinimide, N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and deionized water, adding cysteamine hydrochloride, stirring, centrifuging and washing, to obtain thiol-modified graphene oxide; S3. Grind the M-ZIF / S-doped LiFePO4 precursor and the mercapto-modified graphene oxide, and sinter them at high temperature in a nitrogen atmosphere to obtain a graphene oxide / lithium iron phosphate composite material.
[0007] Furthermore, the usage ratio of the deionized water, hexadecyltrimethylammonium bromide and ethylene glycol is (30-40) mL: (0.5-2) g: (60-70) mL.
[0008] Furthermore, the dosage ratio of LiOH·H2O, H3PO4, FeSO4·7H2O, Na2S2O3, ascorbic acid and partial solution is (1.2-1.5) g: (0.9-1.2) g: (2.7-3) g: (0.1-0.3) g: (0.01-0.03) g: (60-70) mL.
[0009] Furthermore, the pH is adjusted to 6.5-7.
[0010] Furthermore, the usage ratio of the transition metal salt, 2-methylimidazole and the remaining solution is (0.1-0.2) g: (1-2.5) g: (30-40) mL.
[0011] Furthermore, the transition metal salt is one or a combination of Co(NO3)2, Fe(NO3)3, Zn(NO3)2 and NiSO4.
[0012] Furthermore, the heating and stirring is stirring at 40-70° C. for 4-8 hours.
[0013] Furthermore, the heating and stirring is to heat to 180-200° C. at a rate of 5-10° C. / min and then heat for 8-10 h.
[0014] Furthermore, the high temperature sintering is to heat the material to 250-350°C at a rate of 5-10°C / min, calcine for 1.5-2.5h, and then heat the material to 750-800°C at a rate of 5-10°C / min, and calcine for 6-8h.
[0015] Furthermore, the usage ratio of the graphene oxide, N-hydroxysuccinimide, N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride, deionized water and cysteamine hydrochloride is (0.1-0.5) g: (0.3-0.6) g: (0.3-0.9) g: (60-90) mL: (0.05-0.08) g.
[0016] A graphene oxide / lithium iron phosphate composite material is prepared by the above-mentioned graphene oxide / lithium iron phosphate composite material preparation method.
[0017] Beneficial effects of the present invention: (1) The present invention provides a method for preparing a graphene oxide / lithium iron phosphate composite material, which uses graphene oxide and lithium iron phosphate materials for compounding. Since graphene oxide has excellent electrical conductivity, the overall electrical conductivity of the composite material can be significantly improved; in addition, the two-dimensional layer structure of graphene oxide can disperse lithium iron phosphate particles and prevent them from agglomerating, thereby improving the utilization rate of active substances and improving the electrochemical performance of the battery.
[0018] (2) The M-ZIF / S used in the present invention is co-doped with lithium iron phosphate. M-ZIF is a MOF structure formed by transition elements and 2-methylimidazole. Due to its porosity and open skeleton structure, it has a high specific surface area, which is beneficial to increase the contact area between the electrode material and the electrolyte, thereby improving the ion transmission efficiency and electrochemical reaction rate. The doped sulfur atoms replace the positions of some oxygen atoms or phosphorus atoms, promoting the diffusion rate of lithium ions inside the material. In addition, it can make the particles more uniform and fine, and the distribution is more uniform. The synergistic effect of the anion (S) and the cationic group (M-ZIF) in M-ZIF / S can effectively reduce the energy barrier of the electronic energy band transition, improve the electronic conductivity, and enhance the capacity and cycle life of the battery.
[0019] (3) The present invention uses cysteamine hydrochloride to modify graphene oxide with thiol groups, which can not only provide more active sites on the electrode surface and promote the occurrence of electrochemical reactions; in addition, the thiol groups will adsorb the transition metals in M-ZIF, which is beneficial for the graphene oxide to uniformly wrap the lithium iron phosphate and improve the dispersion of the graphene oxide, thereby improving the electrochemical performance of the composite material. DETAILED DESCRIPTION
[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] Example 1 This embodiment provides a graphene oxide / lithium iron phosphate composite material, which is prepared by the following steps: S1. Add 40 mL of deionized water and 1 g of hexadecyltrimethylammonium bromide to 60 mL of ethylene glycol and stir well to obtain a solution; mix 70 mL of the solution with 1.3 g of LiOH·H2O and 1 g of H3PO4, adjust the pH to 7, stir well, then add 2.8 g of FeSO4·7H2O, 0.2 g of Na2S2O3 and 0.02 g of ascorbic acid, and mix well to obtain a mixed solution; mix 30 mL of the solution with 0.15 g of Co(NO3)2 and 1.5 g of 2-methylimidazole, stir at 60°C for 8 h after mixing, and wash by centrifugation to obtain M-ZIF; add M-ZIF to the mixed solution, heat to 180°C at a rate of 5°C / min, and heat for 8 h, wash three times with ethanol and deionized water alternately, and dry at 60°C to obtain M-ZIF / S-doped LiFePO4 precursor; S2, 0.3g of graphene oxide, 0.4g of N-hydroxysuccinimide, 0.6g of N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and 80mL of deionized water were mixed and stirred, 0.06g of cysteamine hydrochloride was added, the mixture was stirred at room temperature for 6h, centrifuged, and washed alternately with ethanol and deionized water three times to obtain thiol-modified graphene oxide; S3. Grind the M-ZIF / S-doped LiFePO4 precursor and thiol-modified graphene oxide to a particle size of 140 mesh, heat to 300°C at a rate of 10°C / min in a nitrogen atmosphere and calcine for 2 h, then heat to 800°C at a rate of 10°C / min and calcine for 8 h to obtain a graphene oxide / lithium iron phosphate composite material.
[0022] Example 2 Compared with Example 1, the difference between this example is that the dosage of Co(NO3)2 and 2-methylimidazole is reduced. The specific implementation steps of S1 are: S1. Add 40 mL of deionized water and 1 g of hexadecyltrimethylammonium bromide to 60 mL of ethylene glycol and stir to obtain a solution; mix 70 mL of the solution with 1.3 g of LiOH·H2O and 1 g of H3PO4, adjust the pH to 7, stir to obtain a solution, add 2.8 g of FeSO4·7H2O, 0.2 g of Na2S2O3 and 0.02 g of ascorbic acid, and mix to obtain a mixed solution; mix 30 mL of the solution with 0.1 g of Co(NO3)2 and 1 g of 2-methylimidazole, stir at 60°C for 8 h after mixing, and wash by centrifugation to obtain M-ZIF; add M-ZIF to the mixed solution, heat to 180°C at a rate of 5°C / min, and heat for 8 h, wash three times with ethanol and deionized water alternately, and dry at 60°C to obtain a M-ZIF / S-doped LiFePO4 precursor; The remaining raw materials and preparation process remain the same as in Example 1.
[0023] Example 3 Compared with Example 1, the difference between this example is that the dosage of Co(NO3)2 and 2-methylimidazole is increased. The specific implementation steps of S1 are: S1. Add 40 mL of deionized water and 1 g of hexadecyltrimethylammonium bromide to 60 mL of ethylene glycol and stir well to obtain a solution; mix 70 mL of the solution with 1.3 g of LiOH·H2O and 1 g of H3PO4, adjust the pH to 7, stir well, then add 2.8 g of FeSO4·7H2O, 0.2 g of Na2S2O3 and 0.02 g of ascorbic acid, mix well to obtain a mixed solution; mix 30 mL of the solution with 0.2 g of Co(NO3)2 and 2.5 g of 2-methylimidazole, stir at 60°C for 8 h after mixing, centrifuge and wash to obtain M-ZIF; add M-ZIF to the mixed solution, heat to 180°C at a rate of 5°C / min and heat for 8 h, wash three times with ethanol and deionized water alternately, and dry at 60°C to obtain M-ZIF / S doped LiFePO4 precursor; The remaining raw materials and preparation process remain the same as in Example 1.
[0024] Example 4 Compared with Example 1, the difference between this example is that "Co(NO3)2" is replaced by "Zn(NO3)2", and the specific implementation steps of S1 are: S1. Add 40 mL of deionized water and 1 g of hexadecyltrimethylammonium bromide to 60 mL of ethylene glycol and stir well to obtain a solution; mix 70 mL of the solution with 1.3 g of LiOH·H2O and 1 g of H3PO4, adjust the pH to 7, stir well, then add 2.8 g of FeSO4·7H2O, 0.2 g of Na2S2O3 and 0.02 g of ascorbic acid, and mix well to obtain a mixed solution; mix 30 mL of the solution with 0.15 g of Zn(NO3)2 and 1.5 g of 2-methylimidazole, stir at 60°C for 8 h after mixing, and wash by centrifugation to obtain M-ZIF; add M-ZIF to the mixed solution, heat to 180°C at a rate of 5°C / min, and heat for 8 h, wash three times with ethanol and deionized water alternately, and dry at 60°C to obtain M-ZIF / S-doped LiFePO4 precursor; The remaining raw materials and preparation process remain the same as in Example 1.
[0025] Example 5 Compared with Example 1, the difference between this embodiment is that the dosage of Na2S2O3 is increased. The specific implementation steps of S1 are: S1. Add 40 mL of deionized water and 1 g of hexadecyltrimethylammonium bromide to 60 mL of ethylene glycol and stir to obtain a solution; mix 70 mL of the solution with 1.3 g of LiOH·H2O and 1 g of H3PO4, adjust the pH to 7, stir to obtain a solution, add 2.8 g of FeSO4·7H2O, 0.3 g of Na2S2O3 and 0.02 g of ascorbic acid, and mix to obtain a mixed solution; mix 30 mL of the solution with 0.15 g of Co(NO3)2 and 1.5 g of 2-methylimidazole, stir at 60°C for 8 h after mixing, and wash by centrifugation to obtain M-ZIF; add M-ZIF to the mixed solution, heat to 180°C at a rate of 5°C / min, and heat for 8 h, wash three times with ethanol and deionized water alternately, and dry at 60°C to obtain a M-ZIF / S-doped LiFePO4 precursor; The remaining raw materials and preparation process remain the same as in Example 1.
[0026] Example 6 Compared with Example 1, the difference between this embodiment is that the amount of Na2S2O3 is reduced. The specific implementation steps of S1 are: S1. Add 40 mL of deionized water and 1 g of hexadecyltrimethylammonium bromide to 60 mL of ethylene glycol and stir well to obtain a solution; mix 70 mL of the solution with 1.3 g of LiOH·H2O and 1 g of H3PO4, adjust the pH to 7, stir well, then add 2.8 g of FeSO4·7H2O, 0.1 g of Na2S2O3 and 0.02 g of ascorbic acid, and mix well to obtain a mixed solution; mix 30 mL of the solution with 0.15 g of Co(NO3)2 and 1.5 g of 2-methylimidazole, stir at 60°C for 8 h after mixing, and wash by centrifugation to obtain M-ZIF; add M-ZIF to the mixed solution, heat to 180°C at a rate of 5°C / min, and heat for 8 h, wash three times with ethanol and deionized water alternately, and dry at 60°C to obtain M-ZIF / S-doped LiFePO4 precursor; The remaining raw materials and preparation process remain the same as in Example 1.
[0027] Example 7 Compared with Example 1, the difference between this embodiment is that the amount of Co(NO3)2 and 2-methylimidazole is reduced while the amount of Na2S2O3 is increased. The specific implementation steps of S1 are: S1. Add 40 mL of deionized water and 1 g of hexadecyltrimethylammonium bromide to 60 mL of ethylene glycol and stir to obtain a solution; mix 70 mL of the solution with 1.3 g of LiOH·H2O and 1 g of H3PO4, adjust the pH to 7, stir to obtain a solution, add 2.8 g of FeSO4·7H2O, 0.3 g of Na2S2O3 and 0.02 g of ascorbic acid, and mix to obtain a mixed solution; mix 30 mL of the solution with 0.1 g of Co(NO3)2 and 1 g of 2-methylimidazole, stir at 60°C for 8 h after mixing, and wash by centrifugation to obtain M-ZIF; add M-ZIF to the mixed solution, heat to 180°C at a rate of 5°C / min, and heat for 8 h, wash three times with ethanol and deionized water alternately, and dry at 60°C to obtain a M-ZIF / S-doped LiFePO4 precursor; The remaining raw materials and preparation process remain the same as in Example 1.
[0028] Example 8 Compared with Example 1, the difference between this example is that the amount of Co(NO3)2 and 2-methylimidazole is increased while the amount of Na2S2O3 is reduced. The specific implementation steps of S1 are: S1. Add 40 mL of deionized water and 1 g of hexadecyltrimethylammonium bromide to 60 mL of ethylene glycol and stir to obtain a solution; mix 70 mL of the solution with 1.3 g of LiOH·H2O and 1 g of H3PO4, adjust the pH to 7, stir to obtain a solution, add 2.8 g of FeSO4·7H2O, 0.1 g of Na2S2O3 and 0.02 g of ascorbic acid, and mix to obtain a mixed solution; mix 30 mL of the solution with 0.2 g of Co(NO3)2 and 2.5 g of 2-methylimidazole, stir at 60°C for 8 h after mixing, and wash by centrifugation to obtain M-ZIF; add M-ZIF to the mixed solution, heat to 180°C at a rate of 5°C / min, and heat for 8 h, wash three times with ethanol and deionized water alternately, and dry at 60°C to obtain a M-ZIF / S-doped LiFePO4 precursor; The remaining raw materials and preparation process remain the same as in Example 1.
[0029] Example 9 Compared with Example 1, the difference between this example is that the dosage of cysteamine hydrochloride is reduced. The specific implementation steps of S2 are: S2, 0.3g of graphene oxide, 0.4g of N-hydroxysuccinimide, 0.6g of N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and 80mL of deionized water were mixed and stirred, 0.06g of cysteamine hydrochloride was added, the mixture was stirred at room temperature for 6h, centrifuged, and washed alternately with ethanol and deionized water three times to obtain thiol-modified graphene oxide; The remaining raw materials and preparation process remain the same as in Example 1.
[0030] Comparative Example 1 Compared with Example 1, this comparative example differs in that no Na2S2O3 is added, and the specific implementation steps are as follows: S1. Add 40 mL of deionized water and 1 g of hexadecyltrimethylammonium bromide to 60 mL of ethylene glycol and stir well to obtain a solution; mix 70 mL of the solution with 1.3 g of LiOH·H2O and 1 g of H3PO4, adjust the pH to 7, stir well, then add 2.8 g of FeSO4·7H2O and 0.02 g of ascorbic acid, mix well to obtain a mixed solution; mix 30 mL of the solution with 0.15 g of Co(NO3)2 and 1.5 g of 2-methylimidazole, stir at 60°C for 8 h after mixing, centrifuge and wash to obtain M-ZIF; add M-ZIF to the mixed solution, heat to 180°C at a rate of 5°C / min, heat for 8 h, wash three times with ethanol and deionized water alternately, and dry at 60°C to obtain M-ZIF / S doped LiFePO4 precursor; The remaining raw materials and preparation process remain the same as in Example 1.
[0031] Comparative Example 2 Compared with Example 1, this comparative example differs in that Co(NO3)2 and 2-methylimidazole are not added, and the specific implementation steps are as follows: S1. Add 40 mL of deionized water and 1 g of hexadecyltrimethylammonium bromide to 60 mL of ethylene glycol and stir to obtain a solution; mix 70 mL of the solution with 1.3 g of LiOH·H2O and 1 g of H3PO4, adjust the pH to 7, stir to obtain a solution, add 2.8 g of FeSO4·7H2O, 0.2 g of Na2S2O3 and 0.02 g of ascorbic acid, mix to obtain a mixed solution; stir at 60°C for 8 h, centrifuge and wash to obtain M-ZIF; add M-ZIF to the mixed solution, heat to 180°C at a rate of 5°C / min and heat for 8 h, wash three times with ethanol and deionized water alternately, and dry at 60°C to obtain a M-ZIF / S-doped LiFePO4 precursor; The remaining raw materials and preparation process remain the same as in Example 1.
[0032] Comparative Example 3 Compared with Example 1, this comparative example differs in that Co(NO3)2, 2-methylimidazole and Na2S2O3 are not added at the same time, and the specific implementation steps are as follows: S1. Add 40 mL of deionized water and 1 g of hexadecyltrimethylammonium bromide to 60 mL of ethylene glycol and stir evenly to obtain a solution; mix 70 mL of the solution with 1.3 g of LiOH·H2O and 1 g of H3PO4, adjust the pH to 7, stir evenly, then add 2.8 g of FeSO4·7H2O and 0.02 g of ascorbic acid, mix evenly to obtain a mixed solution; stir at 60°C for 8 h, centrifuge and wash to obtain M-ZIF; add M-ZIF to the mixed solution, heat to 180°C at a rate of 5°C / min and heat for 8 h, wash three times with ethanol and deionized water alternately, and dry at 60°C to obtain M-ZIF / S-doped LiFePO4 precursor; The remaining raw materials and preparation process remain the same as in Example 1.
[0033] Comparative Example 4 Compared with Example 1, the difference in this comparative example is that the graphene oxide is not modified with thiol groups, and the specific implementation steps are as follows: S1. Add 40 mL of deionized water and 1 g of hexadecyltrimethylammonium bromide to 60 mL of ethylene glycol and stir well to obtain a solution; mix 70 mL of the solution with 1.3 g of LiOH·H2O and 1 g of H3PO4, adjust the pH to 7, stir well, then add 2.8 g of FeSO4·7H2O, 0.2 g of Na2S2O3 and 0.02 g of ascorbic acid, mix well to obtain a mixed solution; add 0.15 g of Co(NO3)2 and 1.5 g of 2-methylimidazole to 30 mL of the solution, stir well at 60°C for 8 h, centrifuge and wash to obtain M-ZIF; add M-ZIF to the mixed solution, heat to 180°C at a rate of 5°C / min and heat for 8 h, wash three times with ethanol and deionized water alternately, and dry at 60°C to obtain M-ZIF / S-doped LiFePO4 precursor; S2. Grind the M-ZIF / S-doped LiFePO4 precursor and graphene oxide to a particle size of 140 mesh, heat to 300°C at a rate of 10°C / min in a nitrogen atmosphere and calcine for 2 h, then heat to 800°C at a rate of 10°C / min and calcine for 8 h to obtain a graphene oxide / lithium iron phosphate composite material.
[0034] The remaining raw materials and preparation process remain the same as in Example 1.
[0035] Comparative Example 5 Compared with Example 1, this comparative example differs in that no graphene oxide is added, and the specific implementation steps are as follows: S1. Add 40 mL of deionized water and 1 g of hexadecyltrimethylammonium bromide to 60 mL of ethylene glycol and stir well to obtain a solution; mix 70 mL of the solution with 1.3 g of LiOH·H2O and 1 g of H3PO4, adjust the pH to 7, stir well, then add 2.8 g of FeSO4·7H2O, 0.2 g of Na2S2O3 and 0.02 g of ascorbic acid, and mix well to obtain a mixed solution; mix 30 mL of the solution with 0.15 g of Co(NO3)2 and 1.5 g of 2-methylimidazole, stir at 60°C for 8 h after mixing, and wash by centrifugation to obtain M-ZIF; add M-ZIF to the mixed solution, heat to 180°C at a rate of 5°C / min, and heat for 8 h, wash three times with ethanol and deionized water alternately, and dry at 60°C to obtain M-ZIF / S-doped LiFePO4 precursor; S2. Grind the M-ZIF / S-doped LiFePO4 precursor to a particle size of 140 mesh, heat it to 300°C at a rate of 10°C / min in a nitrogen atmosphere and calcine it for 2 hours, then heat it to 800°C at a rate of 10°C / min and calcine it for 8 hours to obtain a lithium iron phosphate composite material.
[0036] The remaining raw materials and preparation process remain the same as in Example 1.
[0037] Performance Testing The graphene oxide / lithium iron phosphate composite materials obtained in Examples 1 to 9 and Comparative Examples 1 to 5 were used as raw materials for positive electrode active materials of button batteries to prepare button batteries. Capacity tests and cycle tests were performed on the prepared button batteries according to SJ / T 11797-2022. The test results are shown in Table 1:
[0038] The electrochemical performance of positive electrode materials can be effectively improved by heterogeneous doping, transition metal doping, conductive polymer coating and carbon coating. Among them, carbon coating is a simple and effective means of improvement. Graphene, as a single-atom-layer carbon material with a two-dimensional honeycomb lattice structure, has a high proportion of sp 2 coordinated carbon, showing more disorder than sp 3 The higher conductivity of coordinated carbon and its high specific surface area provide sufficient conductive space for LiFePO4 / C, significantly improving the electronic conductivity. In addition, transition metal doping can improve the electronic conductivity of the material by introducing additional free electrons or holes, reduce the energy barrier for lithium ion diffusion, thereby increasing the migration rate of lithium ions and improving rate performance.
[0039] As can be seen from Table 1, compared with Example 1, the difference between Example 2-3 is that the amount of Co(NO3)2 and 2-methylimidazole affects the M-ZIF content in the material, and too little content affects the ion transfer efficiency and the electrochemical reaction rate. Due to its porosity and open skeleton structure, too much content will affect the overall stability of the composite material; compared with Example 1, the difference between Example 4 and Example 1 is only the replacement of transition metal ions. As catalytic active centers, transition metal ions can provide abundant active sites, which are helpful to improve the electrochemical reaction efficiency; compared with Example 1, the doped sulfur atoms in Example 5-6 promote the diffusion rate of lithium ions inside the material, and in addition, the particles can be made more uniform and fine, and the distribution is more uniform. Too little doping will correspondingly reduce the electrochemical performance of the material, but too much sulfur doping will cause the conductivity of the material to decrease instead; compared with Example 1, the difference between Example 7-8 and Example 1 is the ratio of M-ZIF and sulfur source and the adjustment within a reasonable range. From the results, a composite material with good performance can be obtained; compared with Example 1, the reduction in the amount of cysteamine hydrochloride in Example 9 will affect the adsorption of graphene oxide and lithium iron phosphate.
[0040] Combining the data of Comparative Examples 1-3, Examples 7-8 and Example 1, it can be seen that the synergistic effect of the anion (S) and the cationic group (M-ZIF) in M-ZIF / S can effectively reduce the energy barrier of the electron energy band transition, thereby improving the electronic conductivity and enhancing the capacity and cycle life of the battery; Comparative Example 4 and Example 9 compared with Example 1 show that the thiol-modified graphene oxide can not only promote the occurrence of electrochemical reactions; in addition, the thiol group and the transition metal in M-ZIF will be adsorbed to enhance the stability of the composite material; Comparative Example 5 compared with Example 1, after not adding graphene oxide, the capacity and cycle life of the battery of the composite material both show a downward trend.
[0041] In summary, the present invention provides a graphene oxide / lithium iron phosphate composite material and a preparation method thereof. The prepared graphene oxide / lithium iron phosphate composite material has high battery capacity and cycle stability, and has good application prospects in the field of lithium iron phosphate material technology.
[0042] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0043] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a graphene oxide / lithium iron phosphate composite material, characterized in that: The following steps are involved: S1. Prepare a solution, mix part of the solution with LiOH·H2O and H3PO4, adjust the pH, stir evenly, then add FeSO4·7H2O, Na2S2O3 and ascorbic acid, mix evenly to obtain a mixed solution; mix the remaining solution with a transition metal salt and 2-methylimidazole, heat and stir, centrifuge and wash to obtain M-ZIF; add M-ZIF to the mixed solution, heat and stir, wash and dry to obtain a M-ZIF / S-doped LiFePO4 precursor; S2, preparing thiol-modified graphene oxide; S3, grinding the M-ZIF / S-doped LiFePO4 precursor and the thiol-modified graphene oxide, and sintering them at high temperature in a nitrogen atmosphere to obtain a graphene oxide / lithium iron phosphate composite material; The solution is deionized water and hexadecyltrimethylammonium bromide added to ethylene glycol and stirred evenly; The M-ZIF is a MOF structure formed by transition metal and 2-methylimidazole.
2. The method for preparing a graphene oxide / lithium iron phosphate composite material according to claim 1, characterized in that: The dosage ratio of LiOH·H2O, H3PO4, FeSO4·7H2O, Na2S2O3, ascorbic acid and partial solution is (1.2-1.5) g: (0.9-1.2) g: (2.7-3) g: (0.1-0.3) g: (0.01-0.03) g: (60-70) mL; The pH was adjusted to 6.5-7.
3. The method for preparing a graphene oxide / lithium iron phosphate composite material according to claim 1, characterized in that: The ratio of the transition metal salt, 2-methylimidazole and the remaining solution is (0.1-0.2) g: (1-2.5) g: (30-40) mL; The transition metal salt is one or a combination of Co(NO3)2, Fe(NO3)3, Zn(NO3)2 and NiSO4.
4. The method for preparing a graphene oxide / lithium iron phosphate composite material according to claim 1, characterized in that: The heating stirring is stirring at 40-70°C for 4-8h; the heating stirring is heating to 180-200°C at a rate of 5-10°C / min, and then heating for 8-10h.
5. The method for preparing a graphene oxide / lithium iron phosphate composite material according to claim 1, characterized in that: The high temperature sintering is to heat up to 250-350°C at a rate of 5-10°C / min, calcine for 1.5-2.5h, and then heat up to 750-800°C at a rate of 5-10°C / min, and calcine for 6-8h.
6. The method for preparing a graphene oxide / lithium iron phosphate composite material according to claim 1, characterized in that: The usage ratio of the deionized water, hexadecyltrimethylammonium bromide and ethylene glycol is (30-40) mL: (0.5-2) g: (60-70) mL.
7. The method for preparing a graphene oxide / lithium iron phosphate composite material according to claim 1, characterized in that: The thiol-modified graphene oxide is prepared by the following steps: Graphene oxide, N-hydroxysuccinimide, N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and deionized water are mixed and stirred, cysteamine hydrochloride is added, stirred, and centrifuged and washed to obtain thiol-modified graphene oxide.
8. The method for preparing a graphene oxide / lithium iron phosphate composite material according to claim 7, characterized in that: The usage ratio of the graphene oxide, N-hydroxysuccinimide, N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride, deionized water and cysteamine hydrochloride is (0.1-0.5) g: (0.3-0.6) g: (0.3-0.9) g: (60-90) mL: (0.05-0.08) g.
9. A graphene oxide / lithium iron phosphate composite material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method of lithium iron phosphate / graphene oxide composite material
CN115924899A
Preparation method and application of metal-doped carbon in-situ coated lithium iron phosphate electrode material
CN114551823A
Positive electrode material for lithium iron phosphate battery and preparation method of positive electrode material
CN118619234A
Preparation method for high-performance lithium iron phosphate and use thereof
US20240409469A1